Index — volume 28 — 1973 (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La politisation des relations du travail (Relations industrielles / Industrial Relations, 1973)
Nous publions ici un résumé des travaux présentés lors du dernier Congrès des relations industrielles de Laval, les 30 avril et 1er mai 1973. Les textes complets paraîtront prochainement dans un ouvrage intitulé La politisation des relations du travail.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le coût d’une convention collective (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Adjudication of Grievances in Public Service of Canada - Aggarwal, Arjun P. (Relations industrielles / Industrial Relations, 1973)
Employer-employee relations in the Federal Public Service of Canada entered a new era with the proclamation on March 13, 1967, of three Acts— The Public Service Staff Relations Act ; The Public Service Employment Act ; and an Act to Amend the Financial Administration Act. The employees have been guaranteed the right to organize, the right to bargain, the right to strike and the right to get grievances adjudicated by an independent tribunal. The statutory right to grieve and get the grievances adjudicated have provided the federal public employees with a sense of justice and « fairplay ». The adjudication system has made the private sector of industrial jurisprudence applicable to federal public services with remarkable success. This article deals with the function and operation of the statutory Grievance Process and Adjudication.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Profil psychologique des étudiants canadiens-français au M.B.A. : conséquences pour une politique de sélection - Allaire, Yvan; Toulouse, Jean-Marie (Relations industrielles / Industrial Relations, 1973)
Cet article présente les résultats d'une étude du profil psychologique d'étudiants canadiens-français inscrits dans des programmes de maîtrise en administration des affaires (M.B.A.). L'objectif de l'étude est de comparer le profil de ces étudiants aux profils de l'entrepreneur et du« manager » suggérés par les études sur ces deux types d'agent économique. Dans l'ensemble les étudiants ont un profil se rapprochant davantage du« manager » que de l'entrepreneur ; cependant une forte proportion d'entre eux montre un profil se rapprochant ni de l'entrepreneur ni du manager. On montre de plus comment cette information pourrait être utilisée pour formuler une politique de sélection des candidats à un programme de M.B.Â.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Prices and Incomes Commission in Retrospect - Anton, F. R. (Relations industrielles / Industrial Relations, 1973)
In this article, the author reviews the Canadian Prices and Incomes Commission's findings and comments on some of the conclusions drawn.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

A Comparison of Weighted and Unweighted Intergroup Climate Satisfaction Scores - Barth, R. T. (Relations industrielles / Industrial Relations, 1973)
Perceptions of the configuration and quality of intergroup climates by 256 engineer-scientists in ten R & D organizations were factor analyzed. Five reliable dimensions evolved which accounted for 65% of the 68-item total variance. For each of these dimensions, the relationships between three combinations of level of attainment, level of aspiration, and level of urgency are explored separately and the combined impact of each combination on overall satisfaction with intergroup communication is examined. The findings suggest that unweighted scores provide better predictors of overall satisfaction with intergroup communication than do scores weighted by urgency ratings. Results lend empirical weight to studies in which the utility of weighted versus unweighted scores in the prediction of job satisfaction were explored.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Rezler on Automation and Employment - Beach, Earl F. (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

An American Philosophy of Social Security - Beausoleil, Gilles (Relations industrielles / Industrial Relations, 1973)
This article reviews "An American Philosophy of Social Security" by J. Douglas Brown.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

College Graduates and Jobs, Adjusting to a New Labor Market Situation - Bélanger, Gérard (Relations industrielles / Industrial Relations, 1973)
This article reviews "College Graduates and Jobs, Adjusting to a New Labor Market Situation" by The Carnegie Commission on Higher Education.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Professors, Unions, and American Higher Education - Bélanger, Gérard (Relations industrielles / Industrial Relations, 1973)
This article reviews "Professors, Unions, and American Higher Education" by Everett Carl Ladd, Jr., and Seymour Martin Lipset.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Éléments d’économie pour travailleurs sociaux - Bélanger, Gilles (Relations industrielles / Industrial Relations, 1973)
This article reviews "Éléments d’économie pour travailleurs sociaux" by Fr. Pereira De Moura.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le rôle d’un service du personnel dans une administration scolaire plus humaine - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1973)
En appliquant la notion de système aux institutions scolaires, l’auteur établit les grandes lignes de ce que serait une administration scolaire plus humaine et redéfinit le rôle de l'administration du personnel dans ce nouveau contexte.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Studies in Managerial Process and Organizational Behavior - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1973)
This article reviews "Studies in Managerial Process and Organizational Behavior" by John H. Turner, Allan C. Filley and Robert J. House.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Engineer in the Industrial Corporation - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1973)
This article reviews "The Engineer in the Industrial Corporation" by Richard R. Ritti.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Atlas de l’emploi : Ville et île de Montréal - Belzile, Bertrand (Relations industrielles / Industrial Relations, 1973)
This article reviews "Atlas de l’emploi : Ville et île de Montréal" by Claude Marois.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labour Economics in Canada - Belzile, Bertrand (Relations industrielles / Industrial Relations, 1973)
This article reviews "Labour Economics in Canada" by Sylvia Ostry and Mahmood A. Zaidi.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les partenaires sociaux face aux problèmes de productivité et d’emploi - Belzile, Bertrand (Relations industrielles / Industrial Relations, 1973)
This article reviews "Les partenaires sociaux face aux problèmes de productivité et d’emploi" by Yves Delamotte.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Work in American Society - Belzile, Bertrand (Relations industrielles / Industrial Relations, 1973)
This article reviews "Work in American Society" by Seymour Wolfbein.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Organized Labour and the Imperial Munitions Board - Bercuson, D. J. (Relations industrielles / Industrial Relations, 1973)
The author examines the fight for fair wage clauses in Canadian munitions production at the beginning of this century.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Canadian Cases in Labour Relations and Collective Bargaining - Bernier, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Canadian Cases in Labour Relations and Collective Bargaining" by Hem C. Jain.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Contemporary Collective Bargaining - Bernier, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Contemporary Collective Bargaining" by Harold W. Davey.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Industrial Relations Systems - Bernier, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Industrial Relations Systems" by John T. Dunlop.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor Relations Law - Bernier, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Labor Relations Law" by Benjamin J. Taylor and Fred Witney.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Bargaining : Monopoly versus Union Power - Boivin, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Bargaining : Monopoly versus Union Power" by George de Menil.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

City Employee Bargaining with a Divided Management - Boivin, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "City Employee Bargaining with a Divided Management" by Thomas A. Kochan.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Collective Bargaining by Public Employees in Canada : Five Models - Boivin, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Collective Bargaining by Public Employees in Canada : Five Models" by H.W. Arthurs.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Collective Bargaining in the Public Service - Boivin, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Collective Bargaining in the Public Service" from The Institute of Public Administration of Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Dispute Settlement in the Public Sector - Boivin, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Dispute Settlement in the Public Sector" edited by Thomas P. Gilroy.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Disputes Procedure in Action - Boivin, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Disputes Procedure in Action" by Richard Hyman.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Government as Employer - Boivin, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Government as Employer" by Sterling D. Spero.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Government Employees and Collective Bargaining, Hawaii PERB : Year One - Boivin, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Government Employees and Collective Bargaining, Hawaii PERB : Year One" edited by John B. Ferguson and Joyce M. Najita.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les coûts et l’efficacité dans les hôpitaux canadiens - Boivin, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Les coûts et l’efficacité dans les hôpitaux canadiens" by R.D. Fraser.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Public Employment Bibiography - Boivin, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Public Employment Bibiography" by Robert V. Pezdek.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Strike, For and Against - Boivin, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "The Strike, For and Against" edited by Harold H. Hart.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La dispersion régionale du taux de chômage structurel canadien - Boucher, Michel (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’obligation de négocier : une décision étonnante - Breton, Réjean (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La protection de la formation d’un syndicat - Breton, Réjean (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Loi sur les relations de travail dans l’industrie de la construction - Breton, Réjean (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Federation Expulsions and Union Mergers in the United States - Chaison, Gary N. (Relations industrielles / Industrial Relations, 1973)
While the frequency of mergers among unions in the United States has only recently increased, mergers have played a major role in the affairs of unions expelled from federations (AFL, CIO and AFL-CIO) since 1949. An examination of the seventeen expelled unions indicates that only two have entirely disbanded and only one has returned directly to its federation. The remaining expelled unions merged with or into either their rival affiliates or other expelled unions. It is suggested that this high incidence of mergers was the results of the manner in which isolation induced exiles to merge while also reducing previously formidable barriers.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Selected Models of Worker Education in Europe - Chaison, Gary N. (Relations industrielles / Industrial Relations, 1973)
This article reviews "Selected Models of Worker Education in Europe" from Research Series III, by Robert E. Beldings.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le syndicalisme des professeurs d’université – Quelques réflexions - Chung, Joseph H. (Relations industrielles / Industrial Relations, 1973)
Dans un premier temps, cet article se penche sur le mouvement syndicaliste et para-syndicaliste des professeurs d'université tant au Canada qu'aux États-Unis. Dans une seconde étape, l'auteur considère les raisons de leur syndicalisation, ses implications et son avenir.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Shiners' War: Social Violence in the Ottawa Valley in the 1830s - Cross, Michael S. (Canadian Historical Review, 1973)
This article provides social, ethnic and class perspectives on the turmoil, known as the Shiners' War, in the Ottawa Valley in the 1830s. The author concludes that "...the time of the lower orders had not yet come. In the Shiners War, the ultimate victory of the [upper] classes over the masses was a near-inevitability."

British Trade Unions and the Problem of Change - Dion, Gérard (Relations industrielles / Industrial Relations, 1973)
This article reviews "British Trade Unions and the Problem of Change" by Will Paynter.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Comparative Labor Movements : Ideological Roots and Institutional Developments - Dion, Gérard (Relations industrielles / Industrial Relations, 1973)
This article reviews "Comparative Labor Movements : Ideological Roots and Institutional Developments" by Adolf Sturmthal.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

European Labor Relations in the 70’s, An Overview - Dion, Gérard (Relations industrielles / Industrial Relations, 1973)
This article reviews "European Labor Relations in the 70’s, An Overview" from Management Counsellors International (Brussels).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Industrial Relations in Canada - Dion, Gérard (Relations Industrielles / Industrial Relations, 1973)
This article reviews the book, "Industrial Relations in Canada," second edition, by Stuart Jamieson.

Le monde ouvrier au Québec - Dion, Gérard (Relations industrielles / Industrial Relations, 1973)
This article reviews the retrospective bibliography "Le monde ouvrier au Québec" by André E. LeBlanc et James D. Thwaites.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Reuther - Dion, Gérard (Relations industrielles / Industrial Relations, 1973)
This article reviews "Reuther" by Frank Cormier and William J. Eaton.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The History of Management Thought - Dion, Gérard (Relations industrielles / Industrial Relations, 1973)
This article reviews "The History of Management Thought" by Claude George, Jr.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Beyond the Strike Statistics - Finn, Ed (Relations industrielles / Industrial Relations, 1973)
Before examining many of the myths surrounding the strike phenomenon, the author of this paper feels that the accuracy of the strike figures themselves should be questioned.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Perspectives on the Wage-Price-Unemployment Problem : Stop the Market, I Want to Get Off - Fortin, Pierre (Relations industrielles / Industrial Relations, 1973)
This article reviews "Perspectives on the Wage-Price-Unemployment Problem : Stop the Market, I Want to Get Off" edited by Vance F. Mitchell and W.T. Stanbury.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Nationalism and the Multinational Enterprise - Garnier, Gérard (Relations industrielles / Industrial Relations, 1973)
This article reviews "Nationalism and the Multinational Enterprise" by R.H. Hahlo, G. Smith et R. Wright.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Dispute Settlement in the Public Sector : The Canadian Scene - Goldenberg, Shirley B. (Relations industrielles / Industrial Relations, 1973)
A brief overview of the current provisions for impasse resolution at all levels of public employment is followed by a more detailled discussion of policy and practice in jurisdictions that grant the right to strike to the employees of senior levels of government. Finally, the author tries to identify some of the problems that complicate the settlement of disputes in the public sector and considers the challenge and the prospects of resolving these problems in the light of the Canadian experience.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Employment Impact of Fringe Benefits in Canadian Manufacturing Sector : 1957-1965 - Hameed, Syed M.A. (Relations industrielles / Industrial Relations, 1973)
The paper analyzes the growing costs of various fringe benefits in Canada and their impact on expanding employment. The empirical evidence is in support of fringe barrier hypothesis but not until labour turnover costs are added to fringe costs. It emphasizes that Canadian data on fringe benefits and overtime are extremely inadequate therefore, at the present time, no conclusive study is possible without collecting data on overtime, describing the causes of assigning it internally in a factory. This study attempted to fill in this gap by suggesting that external factors such as skill shortages and capacity output are not significant determinants of overtime.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La Loi 9 et les relations de travail dans l’industrie de la construction au Québec - Hébert, Gérard (Relations industrielles / Industrial Relations, 1973)
En 1973 le gouvernement du Québec, par la loi 9, modifiait substantiellement la Loi sur les relations du travail dans l'industrie de la construction. L'auteur souligne ces changements et en expose les conséquences.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Multinational Corporation and Industrial Relations : The American Approach - Heise, Paul A. (Relations industrielles / Industrial Relations, 1973)
The special problems that the MNC presents in the context of the American industrial relations system has led the U.S. unions, to respond with a call for controls on trade. Europeans, in a different context, are responding to the integration of Europe and the imposition of some aspects of the U.S. system by U.S. corporations in Europe. The problems of understanding each other's goals will be difficult, but controls on the MNCs could serve both.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Practice of Collective Bargaining - Isbester, Fraser (Relations industrielles / Industrial Relations, 1973)
This article reviews "The Practice of Collective Bargaining" by Edwin F. Beal, Edward D. Wickersham and Philip Kienast.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Current Objectives of Canadian Federal Manpower Programs - Jain, Harish C.; Hines, Robert J. (Relations industrielles / Industrial Relations, 1973)
In this paper some of the factors leading to renewed interest in Manpower in the 1960's are enumerated ; the present course of Federal Manpower Programs is examined and the objectives of these programs are evaluated. It is suggested that the emphasis of the Federal Manpower Programs on economic growth and stabilization of the economy is misguided ; that the Department of Manpower and Immigration has failed to foresee shifts in labour market composition ; and that in the face of counter-productive fiscal policy, manpower programs and objectives as originally conceived do not have the capability to resurrect a sick economy.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

A Cross-Cultural Study of Worker Attitudes in a Bicultural Economic Environment - Kothari, Vinay (Relations industrielles / Industrial Relations, 1973)
This research study examines the attitudes of French and English workers of New Brunswick, and it attempts to show similarities and differences in the attitudes of the two cultural groups. Specifically, the worker's attitudes towards his co-workers, economic benefits, administrative practices, physical conditions, and the work itself are examined and analyzed. Overall, the study points out that there are no significant differences between the attitudes of French and those of English. But the differences are likely to increase in the years to come because of social trends.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Effective Management, Social Psychological Approach - Ladouceur, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Effective Management, Social Psychological Approach" by David J. Lawless.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Programmes Learning Aid for Personnel Administration - Ladouceur, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Programmes Learning Aid for Personnel Administration" by George S. Odiorne.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Taux du Syndicalisme au Québec - Laflamme, Gilles (Relations industrielles / Industrial Relations, 1973)
This article reviews "Taux du Syndicalisme au Québec" from the Ministère du travail et de la main-d’oeuvre (Québec).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Operations Research for Managerial Decisions - Langevin, Jean-Louis (Relations industrielles / Industrial Relations, 1973)
This article reviews "Operations Research for Managerial Decisions" by Donald R. Plane and Gary A. Kochenberger.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Where Have All the Robots Gone? Worker Dissatisfaction in the 70’s - Larouche, Viateur (Relations industrielles / Industrial Relations, 1973)
This article reviews "Where Have All the Robots Gone? Worker Dissatisfaction in the 70’s" by Harold L. Sheppard and Neal Q. Herrick.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Satisfaction au travail : problèmes associés à la mesure - Larouche, Viateur; Levesque, André; Delorme, François (Relations industrielles / Industrial Relations, 1973)
Le présent article s'inscrit dans la suite logique d'un texte précédemment publié. Les auteurs y dépouillent une variété de définitions opérationnelles de la satisfaction au travail à partir desquelles ils opèrent un choix en accord avec leur position théorique. Ils procèdent ensuite à une revue sommaire des instruments de mesure disponibles et des considérations méthodologiques pertinentes afin de suggérer un devis propre à faciliter l'élaboration d'un instrument de mesure adéquat.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Some Evidence of the Impact on Non-Wage Labour Cost on Overtime Work and Employment - Laudadio, Leonard; Percy, Michael (Relations industrielles / Industrial Relations, 1973)
Total labour costs can be considered to be a function of the hourly wage, a quasi-fixed component (mainly fringe benefits and training cost) and overtime rate. The theoretical model employee in this paper suggests that an increase in the ratio of quasi-fixed cost to overtime rate leads to an increase in the amount of scheduled overtime work instead of employment. The model, tested with Canadian data, yields statistically significant results.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Dimension of Canadian Younth Unemployment : A Theoretical Explanation - Lazar, Fred; Donner, Arthur (Relations industrielles / Industrial Relations, 1973)
This paper looks beneath the national unemployment numbers to examine in detail the dimension of Canada’s youth unemployment problem. After an outline of the empirical dimensions of youth unemployment in Canada, a theoritical framework is set out to explain the particular characteristics of youth unemployment. Finally, some policy recommendations are presented.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le changement du lieu de travail – étude d’un cas de reclassement - Legault, I. A. (Relations industrielles / Industrial Relations, 1973)
This article reviews "Le changement du lieu de travail – étude d’un cas de reclassement" by Grégoire Tremblay with the collaboration of Isabel Romao.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Assessing the Costs and Benefits of Collective Bargaining – the Potential Use of Costing - Levine, Gilbert (Relations industrielles / Industrial Relations, 1973)
This paper presents the union point of view on collective bargaining costing.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Design of a Fringe Benefit Costing Program - MacDonald, Brock D. (Relations industrielles / Industrial Relations, 1973)
In this paper, the author relates his practical experience with fringe benefit costing in British Columbia.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labour Earnings Identity - McKee, A. F. (Relations industrielles / Industrial Relations, 1973)
An earnings identity may be constructed to relate consistently changes in factor earnings, share of income, productivity, unit costs and price deflator. The case of labour is the most relevant, and is readily illustrated by using GNP and Labour Force statistics. These 'global' changes may be linked up in workable fashion with changes in the Consumer Price Index and wage statistics. The attempt to refine the terms of the identity introduces problems of consistency of definition and improves Utile on the crude results.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Occupational Characteristics of Leading Canadian Executives - Moore, Larry F.; Daly, William G. (Relations industrielles / Industrial Relations, 1973)
The purpose of this study is to investigate the geographic origins, the social and educational backgrounds and the occupational and career patterns of top executives in Canadian Companies.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le non-intéressement des travailleurs à l’entreprise : analyse de quelques causes d’ordre juridique - Morin, Fernand (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Docks After Devlin - Peach, D. A. (Relations industrielles / Industrial Relations, 1973)
This article reviews "The Docks After Devlin" by Michael Mellish.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Competition and Collective Bargaining in the Needle Trades, 1910-1967 - Peach, David A. (Relations industrielles / Industrial Relations, 1973)
This article reviews "Competition and Collective Bargaining in the Needle Trades, 1910-1967" by Jesse Thomas Carpenter.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Current Research on the Quality of Working Life - Portigal, Alan H. (Relations industrielles / Industrial Relations, 1973)
In this paper, the author reviews some viewpoints on the quality of working life and indicates research issues.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Évaluation des coûts-avantages de la négociation collective et banque d’expérience en relation de travail - Quinet, Félix (Relations industrielles / Industrial Relations, 1973)
Après avoir énoncé les motifs qui militent en faveur d'une évaluation des coûts-avantages de la négociation collective, l’auteur propose la création d'une Banque de données, explique ce qu'elle devrait contenir et indique les usages que l'on pourrait en faire.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Relations industrielles : Acteurs, auteurs, faits, tendances - Quinet, Félix (Relations industrielles / Industrial Relations, 1973)
This article reviews "Relations industrielles : Acteurs, auteurs, faits, tendances" by Dimitri Weiss
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Management Decisions and Behavior - Rainville, Jean-Marie (Relations industrielles / Industrial Relations, 1973)
This article reviews "Management Decisions and Behavior" by Max D. Richards and Paul S. Greelaw.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Technologie, structure administrative et mode d’adaptation des individus à l’organisation - Rainville, Jean-Marie (Relations industrielles / Industrial Relations, 1973)
L'hypothèse qui consiste à soutenir que la technologie exerce une influence déterminante sur les structures administratives et les modes d'adaptation des individus à l'organisation doit être révisée. Elle met trop facilement de côté, sans que les auteurs concernés ne le justifient, l'aspect institutionnel des structures administratives dont résultent justement les modes d'adaptation des individus à l'organisation. C'est en ces termes que l'auteur fait l'examen critique des recherches axées sur la variable« technologie ».
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Industrial Conflict and Industrial Relations in Italy : New Perspectives - Ramirez, Bruno C. (Relations industrielles / Industrial Relations, 1973)
The author traces the changes which have occurred in Italy's industrial relations systems as a result of the great wave of strikes of 1969. Special emphasis is placed on the emergence of new structures of workers' representation at the plant level, and on the effect these have had on the method of negotiation.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Relations d’arbitrage et politique économique - Raynaud, André (Relations industrielles / Industrial Relations, 1973)
L'auteur passe en revue les principaux travaux récents sur la relation d'arbitrage et souligne les incertitudes qui entourent cette notion et son utilisation pour la prise de décision. Suite à une brève présentation de résultats obtenus à partir d'un modèle plus complexe que les traditionnelles relations bi-dimensionnelles d'arbitrage, l'auteur s'attache aux conséquences pour la politique économique de la mise en question de la stabilité et de l'existence même de cette relation. Il souligne alors l'importance des politiques de gestion de la demande et compare les coûts respectifs de l'inflation et du sous-emploi.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Workers’ Management and Worker’s Wages in Yugoslavia – the Theory and Practice of Participatory Socialism - Rondeau, Claude (Relations industrielles / Industrial Relations, 1973)
This article reviews "Workers’ Management and Worker’s Wages in Yugoslavia – the Theory and Practice of Participatory Socialism" by Howard M. Wachtel.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Accreditation and the Construction Industry : Five Approaches to Countervailing Employer Power - Rose, Joseph B. (Relations industrielles / Industrial Relations, 1973)
In this paper, the author aims at describing the various legislative approaches to accreditation which have been adopted and at evaluating the strengths and weaknesses of different efforts to reduce employer fragmentation and redress the imbalance of power within the industry.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Des loisirs : pour quoi faire? - Roy, André (Relations industrielles / Industrial Relations, 1973)
This article reviews "Des loisirs : pour quoi faire?" by Jean Fourastié.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’unité de négociation en matière d’accréditation - Roy, André (Relations industrielles / Industrial Relations, 1973)
La détermination des groupes distincts ou des unités de négociation est une des questions les plus complexes dans le domaine des relations du travail. L'auteur tente de cerner ici les principaux critères qui servent à fixer le cadre de la négociation collective dans une société en perpétuelle et rapide évolution.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Politique et technique de direction du personnel - Roy, André (Relations industrielles / Industrial Relations, 1973)
This article reviews "Politique et technique de direction du personnel" by Jean Diverrez.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Répertoire de décisions en application du Code du travail (Tome I – Accréditation et questions connexes) - Roy, André (Relations industrielles / Industrial Relations, 1973)
This article reviews "Répertoire de décisions en application du Code du travail (Tome I – Accréditation et questions connexes)" by J. Gaston Descôteaux.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Ruminations on the « Benefit » Package - Schultz, L. Lawrence (Relations industrielles / Industrial Relations, 1973)
The author reviews the evidence to see if there is general agreement on the definition of fringe benefits and examines the difficulties encountered in computing the benefits.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Collective Bargaining and the Challenge of New Technology - Sexton, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Collective Bargaining and the Challenge of New Technology" from the International Labour Office (Geneva).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Investment in Human Resources and Manpower Planning - Sexton, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews the United Nations paper "Investment in Human Resources and Manpower Planning" presented to the eighth session of Senior Economic Advisers to ECE governments.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’évaluation des programmes de main-d’oeuvre : Observations méthodologiques - Sexton, Jean (Relations industrielles / Industrial Relations, 1973)
Dans cet article, l'auteur présente les origines, la nature, la méthodologie et les limites de l'évaluation des programmes de main-d'oeuvre.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Readings in Labor Economics and Labor Relations - Sexton, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "Readings in Labor Economics and Labor Relations" edited by Richard L. Rowan.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Economics of Technological Change - Sexton, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "The Economics of Technological Change" edited by Nathan Rosenberg.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Politics of Comprehensive Manpower Legislation - Sexton, Jean (Relations industrielles / Industrial Relations, 1973)
This article reviews "The Politics of Comprehensive Manpower Legislation" by Roger H. Davidson.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Economics of Work and Pay - Smith, Douglas A. (Relations industrielles / Industrial Relations, 1973)
This article reviews "The Economics of Work and Pay" by Albert Rees.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le syndicalisme québécois - Solasse, Bernard (Relations industrielles / Industrial Relations, 1973)
This article reviews "Le syndicalisme québécois" by Louis-Marie Tremblay.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Unemployement and Labour Force Participation : The Canadian Experience - Swidinsky, Robert (Relations industrielles / Industrial Relations, 1973)
In an analysis of the short-run sensitivity of the Canadian labour force time series regression results appear inconclusive whereas cross-section regression results suggest a strong negative response to unemployment. Generally, the findings from the cross-section are comparable neither qualitatively nor quantitatively with those from the time series.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les Chevaliers du travail et le Cardinal Taschereau - Sylvain, Philippe (Relations industrielles / Industrial Relations, 1973)
L'auteur explique le rôle joué par l'archevêque de Québec dans la condamnation des Chevaliers du travail par l'Église catholique en 1884. Il montre comment cette censure a été relevée en 1887 grâce à l'intervention de l'archevêque de Baltimore.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Mesure des coûts d’une convention collective : quelques aspects – divers avantages - Vachon, Pierre-André (Relations industrielles / Industrial Relations, 1973)
Cet article tente de regrouper autour de deux pratiques de calcul, à savoir l'estimation et l'évaluation des coûts, les méthodes ou techniques habituellement utilisées dans les entreprises.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor Courts and Grievance Settlement in Western Europe - Verge, Pierre (Relations industrielles / Industrial Relations, 1973)
This article reviews "Labor Courts and Grievance Settlement in Western Europe" edited by B. Aaron.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le droit du travail - Verge, Pierre (Relations industrielles / Industrial Relations, 1973)
This article reviews "Le droit du travail" by Pierre-D. Ollier.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Questions of Public Policy for the Consideration of Periodic Revisions in the Minimum Wage - Waisglass, Harry J. (Relations industrielles / Industrial Relations, 1973)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Factions in British and American Unions – A Comparative Structural Approach - Warner, Malcolm; Edelstein, J. David (Relations industrielles / Industrial Relations, 1973)
In this paper, the authors attempt to discuss the relationship between intra-organizational conflict and factionalism, and how this manifests itself in different ways in British and American unions. They start with a discussion of conflict, then attempt to set out the characteristics of fractions, They next look at factionalism comparatively, and finally attempt an analytical framework which looks at the dimensions of factionalism.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les nouveaux marchands d’hommes? Étude du travail intérimaire - Weiss, Dimitri (Relations industrielles / Industrial Relations, 1973)
This article reviews "Les nouveaux marchands d’hommes? Étude du travail intérimaire" by Guy Caire.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Collective Bargaining in the Public Sector : A Re-Examination - Williams, C. Brian (Relations industrielles / Industrial Relations, 1973)
This paper calls for a new direction in the study of public sector collective bargaining away from the «issue» and «problem» approach in favor of a re-examination, in the light of our experience over the past decade, of the physiology of the technique itself with particular reference to the appropriateness of current public sector collective bargaining structures.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z